Amir evaluated 5x – (x + 3)2 for x = 2, as shown. Describe Amir’s mistake and find the correct answer. 5(2) – (2 + 3)2 = 10 + (-5)2 = 10 + 2

Question

Amir evaluated 5x – (x + 3)2 for x = 2, as shown. Describe Amir’s mistake and find the correct answer. 5(2) – (2 + 3)2 = 10 + (-5)2 = 10 + 25 = 35

0

Answers ( No )

    0
    2022-01-05T23:22:37+00:00

    5 \times 2 - (2 + 3) \times 2 = 10 - 5 \times 2 = 10 - 10 = 0

    0
    2022-01-05T23:22:38+00:00

    Answer with Step-by-step explanation:

    We are given a expression:

    5x - (x + 3)^2

    and we have to evaluate it at x=2

    Putting x=2 in above expression, we get

    5\times 2 - (2 + 3)^2\\\\=10-5^2\\\\=10-25\\\\=-15

    Amir’s Calculation is as follows:

    5(2) - (2 + 3)^2 = 10 + (-5)^2 = 10 + 25 = 35

    He took the minus sign before the bracket of (2+3)² inside the bracket

    i.e. instead of writing -(2+3)²= -5²= -25

    he wrote it as -(2+3)²= (-5)²

    and the correct answer is:

    -15

Leave an answer

Browse
Browse